German Noun Plurals: A Challenge to the Dual-Mechanism Model - Penke, Martina; Krause, Marion (Brain and language, 2002)
In this article, the authors test one of the central claims of the Dual-Mechanism Model (Pinker & Prince, 1994), that is, that regular inflection equals default inflection. Based on results from an elicitation task with eight agrammatic Broca's aphasics and a lexical decision task with unimpaired subjects, the authors show that this assumption is not borne out. Their data on German plural inflection rather indicate that regular inflection is not necessarily identical to default inflection. To capture the German data, they have to assume regular but input-restricted inflection besides regular default inflection.